(untitled) (Manila, Philippines, 1988)
The workshop yielded a number of innovative ideas such as additional crops ( sunflower, early-maturing rice,..) before along with, or after DWR, ratooning of DWR, use rice herbage from the DWR crop, methods for screening for ufra nematode and yellow stem borer
Keywords: Deepwater rice,Nghiên cứu lúa nước; Congresses